A mid-latitude Maastrichtian palynological record from the Yacoraite Formation (Salta Group), northwestern Argentina. (December 2022) - Llorens, Magdalena; Pérez Loinaze, Valeria S.; Narváez, Paula L.; Zelaya, Alfredo M.; Pincheira, Egly Pérez; Gorustovich, Sergio
Abstract: A palynological assemblage from one sample of the Yacoraite Formation outcrops (Maastrichtian–Danian of the Salta Basin) at the Valle del Tonco, Salta Province, Argentina, is described. The flora is distinctly continental and dominated by angiosperms, accompanying ferns and gymnosperms, along with few freshwater algae, bryophytes and fungi. The presence of taxa such as Aquillapollenites magnus, Gabonisporis vigorouxii and Crassitricolporites brasiliensis, together with the absence of typical taxa of the Danian Mtchedlishvilia saltenia Zone, allow to propose a late Maastrichtian age for this palynoflora. Due to its location at mid-latitudes, the palynoflora from the Yacoraite Formation is within a transitional or mixed flora zone with closer affinity to the equatorial Palmae Province. Therefore, the recorded flora has a good potential to understand the transition between the floras of low and high latitudes and to know the floristic composition of the area before the K-Pg extinction event. Highlights: Late Maastrichtian palynoflora from Northwestern Argentina with 58 species. First complete palynological record of Yacoraite Formation. Mid-latitude palynoflora with transitional characteristics. Distinctly continental paleoenvironment in a marine transgression scenario.